Germline Editing of Drosophila Using CRISPR-Cas9-Based Cytosine and Adenine Base Editors - Thakkar, Nirav; Hejzlarova, Adela; Brabec, Vaclav; Dolezel, David (The CRISPR journal, 2023)
Target-AID, BE3, and ABE7.10 base editors fused to the catalytically modified Cas9 and xCas9(3.7) were tested for germline editing of the fruit fly Drosophila melanogaster. We developed a guide RNA-expressing construct, white-4gRNA, targeting splice sites in the white gene, an X-chromosome located gene. Using white-4gRNA flies and transgenic lines expressing Target-AID, BE3, and ABE7.10 base editors, we tested the efficiency of stable germline gene editing at three different temperatures. Classical Cas9 generating insertions/deletions by non-homologous end joining served as a reference. Our data indicate that gene editing is most efficient at 28°C, the highest temperature suitable for fruit flies. Finally, we created a new allele of the core circadian clock gene timeless using Target-AID. This base edited mutant allele timSS308-9FL had a disrupted circadian clock with a period of ∼29 h. The white-4gRNA expressing fly can be used to test new generations of base editors for future applications in Drosophila.
Keywords: Cytosine; editace genu; Gene Editing; Drosophila melanogaster; CRISPR-Cas systémy; vodící RNA, systémy CRISPR-Cas; adenin; Adenine; RNA, Guide, CRISPR-Cas Systems; zárodečné buňky; CRISPR-Cas Systems; Animals; Germ Cells; cytosin; zvířata; Drosophila